Response of sweet basil plants (Ocimum basilicum L.) to gibberellin acid (GA3) under salinity (Journal of Hama University, 2025)
The research was conducted during the year 2024 according to a randomized complete design (R.C.D) in three replicates in the village of Al-Hennadi- Lattakia-Syria. The treatments consisted of three levels of gibberellin (100, 200 and 300 μM).. To induce salinity stress, sodium chloride (NaCl) was used at concentrations (6, 12, 18 dmol/cm). Traits such as plant height (cm/plant), number of branches (branch/plant), total leaf surface area (cm2), leaf specific gravity (g/cm2), leaf chlorophyll content (µg/g) and proline (µmol/g) were measured. High salinity concentration led to negative effects on all indicators studied. Foliar treatment with gibberellin acid led to an increase in plant height, total leaf surface area, specific gravity, and leaf chlorophyll content. On the other hand, treatment with gibberellin acid under salinity stress conditions at a low concentration (100 micromol) outperformed all treatments and the control. Therefore, we recommend foliar spraying with gibberellin acid at a concentration of (100 micromol), due to its role in improving the morphological, physiological, and biochemical characteristics of the sweet basil plant.